2005
DOI: 10.1093/aob/mci243
|View full text |Cite
|
Sign up to set email alerts
|

Growth Dynamics of Mechanically Impeded Lupin Roots: does Altered Morphology Induce Hypoxia?

Abstract: The shift in the zone of extension towards the apex in impeded roots coincided with greater vulnerability to hypoxia even after soil was removed. Roots still encased in impeded soil are likely to suffer from marked O2 deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 43 publications
(78 reference statements)
0
28
0
Order By: Relevance
“…Application of a controlled external mechanical pressure through the media or directly to the roots results in similar effects as for compacted soil, i.e. slower axial growth (Hanbury and Atwell, 2005) and consequently reduced length of roots (Barley, 1962;Goss, 1977;Castillo et al, 1982;Veen, 1982;Lindberg and Pettersson, 1985) as well as in root swelling (Abdalla et al, 1969;Veen, 1982;Kuzeja et al, 2001;Hanbury and Atwell, 2005). The morphological changes, especially those concerning root system architecture (reduced root system size, modified branching pattern), but also modifications of the form of individual roots (increased diameter) probably lead to better adaptation of the living organ to unfavourable environmental conditions.…”
Section: Medium Density and Structurementioning
confidence: 96%
See 1 more Smart Citation
“…Application of a controlled external mechanical pressure through the media or directly to the roots results in similar effects as for compacted soil, i.e. slower axial growth (Hanbury and Atwell, 2005) and consequently reduced length of roots (Barley, 1962;Goss, 1977;Castillo et al, 1982;Veen, 1982;Lindberg and Pettersson, 1985) as well as in root swelling (Abdalla et al, 1969;Veen, 1982;Kuzeja et al, 2001;Hanbury and Atwell, 2005). The morphological changes, especially those concerning root system architecture (reduced root system size, modified branching pattern), but also modifications of the form of individual roots (increased diameter) probably lead to better adaptation of the living organ to unfavourable environmental conditions.…”
Section: Medium Density and Structurementioning
confidence: 96%
“…Similarly, alterations in root morphology are accompanied by internal structural changes (for details see Table 2). Swollen roots either have an increased number of cell layers (Wilson et al, 1977) or their cells show modified sizes (Atwell, 1988;Materechera et al, 1991;Hanbury and Atwell, 2005). Reduced root elongation usually accompanies decreasing length of cells (Bengough et al, 2006;Okamoto et al, 2008) and slower cell production (Croser et al, 1999).…”
Section: Internal Structure Of the Physical Body Changes Under Mechanmentioning
confidence: 99%
“…Cortical changes such as the addition of cell layers ( Wilson et al , 1977 ; Colombi et al 2019 ) or the expansion of cortical cells have been observed ( Atwell, 1988 ; Hanbury and Atwell, 2005 ; Colombi et al ., 2017 , 2019 ). For instance, in lupin, which is usually able to penetrate strong soil ( Materechera et al , 1991 ), radial thickening is caused by the swelling of cortical cells, rather than the addition of cell files ( Atwell, 1988 ; Hanbury and Atwell, 2005 ). However, diverse observations have been made for different species and under a range of experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been demonstrated that an increase in soil strength results in a decrease in root elongation in cotton (Taylor & Ratliff, 1969), maize (Bengough & Mullins, 1991), pea (Croser et al, 1999;Iijima & Kato, 2007) and tobacco (Alameda et al, 2012). In addition studies have demonstrated that in response to mechanical impedance, cell length is reduced and the length of the elongation zone shortened (Veen, 1982;Croser et al, 1999;Hanbury & Atwell, 2005;Okamoto et al, 2008). The slowed rate of elongation that occurs in mechanically impeded roots is therefore likely to be due to a reduced rate of cell elongation, as axial tension is increased by stiffening of the cell walls to reduce elongation (Bengough et al, 2006).…”
Section: Introductionmentioning
confidence: 99%